Gender Development in 46,XY DSD: Influences of Chromosomes, Hormones, and Interactions with Parents and Healthcare Professionals - Amy B. Wisniewski (Scientifica)
Variables that impact gender development in humans are difficult to evaluate. This difficulty exists because it is not usually possible to tease apart biological influences on gender from social variables. People with disorders of sex development, or DSD, provide important opportunities to study gender within individuals for whom biologic components of sex can be discordant with social components of gender. While most studies of gender development in people with 46,XY DSD have historically emphasized the importance of genes and hormones on gender identity and gender role, more recent evidence for a significant role for socialization exists and is considered here. For example, the influence of parents’ perceptions of, and reactions to, DSD are considered. Additionally, the impact of treatments for DSD such as receiving gonadal surgeries or genitoplasty to reduce genital ambiguity on the psychological development of people with 46,XY DSD is presented. Finally, the role of multi-disciplinary care including access to peer support for advancing medical, surgical and psychosexual outcomes of children and adults with 46,XY DSD, regardless of sex of rearing, is discussed.